Nama Tuhan dalam Alquran dan Injil Berbahasa Arab - Yuangga Kurnia Yahya (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
This research aimed to understanding the concept of divinity in Arabic culture through lexemes which mean God used in the Qur’an dan Arabic Gospel. Lexeme is a smallest unit of meaning that formes a word. From the lexem, words, phrases, clauses, and discourses are formed according to Arabic’s concept of divinity. This research uses a semantic approach, through discussion on form and meaning, Brown-Yule’ s idea of text and co-text, and Sapir-Whorf hypothesis on culture and language. This research found that the lexeme of Allah (God) has been known by Arabic people before the birth of Islam and Christian. This lexeme means the name of the highest God in Arabic polytheism and was estimated to be used from the fifth century BC. Arabic Christians used this lexeme as the translation of “God” and referred to “The Only One God” about 500 years before Muhammad’s birth. The lexemes of God in the Quran could be named as Allah, Rabb, Ilah, dhmir (ana, anta, huwa, and nahnu), and the names of Allah (sifat-Allah wa asma-Allah), while the lexemes of God in Arabic Gospels are Allah, Rabb, Ilah, ab (father), Yasu’ (Jesus), al-Ruh al-Quds (Holy Spirit), al-Ibn (Son), as-Sayyid (Lord), al-Mu’allim (Master), al-Malik (King), and dhamir (ana, anta, and huwa). The lexeme of Allah, Rabb, and Ilah are found in both the Qur’an and Arabic Gospel, but these lexemes have some differences in word category, sintaxis function, and semantic role. Furthermore, another lexeme are used with same purpose, such as presenting a more complete and more familiar picture of God.